Maqasid al-Shariah and Sustainable Finance: Analyzing the Impact of Green Sukuk Allocation in Indonesia - Arrazi, Muhammad Fakhrul (Muslim Business and Economics Review, 2025)
This research paper examines the application of Maqasid al-Shariah principles in the context of sustainable finance, focusing on the impact of Green Sukuk Allocation in Indonesia. As an Islamic financial instrument, Green Sukuk aims to raise funds for environmentally friendly projects while adhering to shariah principles. This study analyzes the 2023 Green Sukuk Allocation and Impact Report from the Indonesian Ministry of Finance to assess the impact of Green Sukuk in achieving both financial and sustainable development goals. Using a qualitative approach, this paper evaluates how the allocation of green sukuk funds aligns with the objectives of Maqasid al-Shariah, particularly in the preservation of the environment and the promotion of social welfare. The analysis also considers the challenges and opportunities faced in implementing green sukuk as a sustainable financing mechanism. This research finds that the implementation of green sukuk financing in Indonesia aligns with the five essential principles of Maqasid al-Shariah, namely hifz al-deen (preservation of religion), hifz al-nafs (preservation of life), hifz al-aql (preservation of intellect), hifz al-maal (preservation of wealth), and hifz al-nasl (preservation of lineage). Moreover, the implementation of green sukuk financing has also positively impacted multiple sectors in Indonesia. The findings of this study have important implications for policymakers, financial institutions, and investors seeking to promote sustainable development through Islamic finance instruments. The study's insights can inform the design of future green finance policies and strategies, highlighting the role of Islamic finance in achieving both financial and sustainability goals.